Могили скіфських амазонок: типологія та конструктивні особливості - Фіалко, О.Є. (Археологія і давня історія України, 2021)
У статті розглянуто поховання войовниць п’ятьох регіональних груп Європейської Скіфії. Репрезентовано могили 11 типів з варіантами. Проаналізовано характер конструктивних елементів поховальних споруд. Types of burial structures are one of the most reliable ethno-differentiating criterion. They are commonly due to local natural and economic factors that were accepted by the newcomer population along with main characteristics of their own ritual. As for the shape, the graves of Scythian warriors are arbitrarily divided into 11 types with options, which in general make up three main groups: simple pits and more intricate variable chamber constructions such as undercut and catacombs. 303 graves of women with weapons from 267 barrows are known in the territory of European Scythia. More than half of them (55 %) have not been looted. By territorial principle they can be divided into five main groups: 1) Lower Dnipro steppe (or Steppe); 2) Crimea Foothills; 3) Danube-Dnister steppes (or Transnistria); 4) Forest Steppe Dnipro area (or Forest Steppe); 5) Don region (Steppe and partly Forest Steppe). In total, among graves of the Amazons of European Scythia the undercut (alcove) graves are the most represented — 104, inferior to them are catacombs — 99 and pit graves — 80, undefined — 20. However, the indicators for some groups differ significantly. We can mention the following design features of the graves: ground steps and hollow in the bottom of entrance pit, separation of entrance to dromos or chamber etc. Some specific features are also present in the arrangement of internal space of the graves (nishes, wall and ceiling design, floor decoration, arrangement of a funeral bed etc.). So, burial complexes of the female warriors correspond to Scythian regulations, that is, the design of ground and underground elements does not stand out in the burial ground. Here, we are dealing only with regional features typical for community members who lived there.